Repeated Effects of Vigorous Interval Training in Basketball, Running-Biking, and Boxing on the Physical Self-Perceptions of Obese Adolescents. Issue 1 (2nd January 2018) - Rey, Olivier; Vallier, Jean-Marc; Nicol, Caroline; Mercier, Charles-Symphorien; Maïano, Christophe
Abstract : This study aims to examine the repeated effects of three sessions of vigorous interval training (VIT) in basketball, running-biking, and boxing on the physical self-perceptions (PSP) of obese adolescents participating in a dietary program. A sample of 24 obese adolescents performed the consecutive VIT sessions every week for 5 weeks. PSP were measured immediately after each training session. Analyses of covariance were used to examine changes in PSP. The results showed rapid and constant increases in PSP with significant differences according to sex, time, type of VIT, and an interaction of sex by time by type of VIT, mainly for basketball.